Civil society involvement in harm reduction drug policy: reflections on the past, expectations for the future - Aileen O'Gorman; Eberhard Schatz (BMC, 2021)
Abstract Background A range of civil society organisations (CSOs) such as drug user groups, non-governmental/third sector organisations and networks of existing organisations, seek to shape the development of drugs policy at national and international levels. However, their capacity to do so is shaped by the contexts in which they operate nationally and internationally. The aim of this paper is to explore the lived experience of civil society participation in these contexts, both from the perspective of CSOs engaged in harm reduction advocacy, and the institutions they engage with, in order to inform future policy development. Methods This paper is based on the presentations and discussions from a workshop on 'Civil Society Involvement in Drug Policy hosted by the Correlation - European Harm Reduction Network at the International Society for the Study of Drugs Policy (ISSDP) annual conference in Paris, 2019. In the aftermath of the workshop, the authors analysed the papers and discussions and identified the key themes arising to inform CSI in developing future harm reduction policy and practice. Results Civil society involvement (CSI) in policy decision-making and implementation is acknowledged as an important benefit to representative democracy. Yet, the accounts of CSOs demonstrate the challenges they experience in seeking to shape the contested field of drug policy. Negotiating the complex workings of political institutions, often in adversarial and heavily bureaucratic environments, proved difficult. Nonetheless, an increase in structures which formalised and resourced CSI enabled more meaningful participation at different levels and at different stages of policy making. Conclusions Civil society spaces are colonised by a broad range of civil society actors lobbying from different ideological standpoints including those advocating for a 'drug free world' and those advocating for harm reduction. In these competitive arena, it may be difficult for harm reduction orientated CSOs to influence the policy process. However, the current COVID-19 public health crisis clearly demonstrates the benefits of partnership between CSOs and political institutions to address the harm reduction needs of people who use drugs. The lessons drawn from our workshop serve to inform all partners on this pathway.